HUBUNGAN ANTARA POWEROTOT LENGAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP KEMAMPUAN SMASH PADA CLUB SURYA DESA KAWO TAHUN 20017/2018 - Nurifansyah Nurifansyah; Dadang Warta Candra; Andi Anshari Bausad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
Volleyball is a sport that uses hands and the ball should not touch the floor played by two teams, each team totaling six people. Volleyball is one of the sports that is popular in the community. The problem research is stated as;Is there any correlation of arm muscle power and wrist flexibility toward the volleyball smash ability at Surya Club in Kawo in 2017. The purpose of this study is to find out whether or not there is correlation of arm muscle power and wrist flexibilty toward the volleyball smash ability at Surya Club in Kawo in 2017. The instrument in this study is a test to determine the ability of the subject in the variable to be measured. On the wrist flexibility to the ability of smash volleyball at Surya club in Kawo in 2017, the methods used for data collection are interview, observation, documentation, and performance test (a tool or procedure to obtain data). the data analysis used product moment formula. The result of calculation obtained from this research as stated as r-score = 0.414 with N = 12, and significance level 5%, r-score is lower than r-table that is 0.414 < 0.576.The result is not significant, the alternative hypothesis (Ha) proposed is rejected while the null hypothesis (H0) is accepted which means that there is no correlation of arm muscle power and wrist flexibility toward the volleyball smash ability at Surya Club in Kawo in 2017.